Nanoparticle Reshaping and Ion Migration in Nanocomposite Ultrafast Ionic Actuators: The Converse Piezo–Electro–Kinetic Effect. (3rd June 2019) - Chiolerio, Alessandro; Perrone, Denis; Roppolo, Ignazio; Rizza, Giancarlo; Risplendi, Francesca; Stassi, Stefano; Laurenti, Marco; Rajan, Krishna; Chiappone, Annalisa; Bocchini, Sergio; Cicero, Giancarlo; Pandolfi, Paolo; et al.
Abstract: This article reports on the effect of silver nanoparticles (NPs), used as active fillers, on the piezoelectric response of polymer composites. In particular, it is demonstrated that the application of a periodic electric field drives a collective drift of surface atoms of the NPs along the field direction ("electrokinetic effect") which, in turn, creates macroscopic reversible tensile states. Overdriving the system, in high‐field conditions, the electronic current is counterbalanced by a massive injection of Ag + ions into the matrix, producing a metastable exceptional expansion of the device. For similitude with the converse piezoelectric effect, it has been called the converse piezo–electro–kinetic effect. By using in situ spectroscopy, vibrometric analysis, real‐time UV‐visible spectroscopy, in situ electrical transmission electron microscopy, and in qualitative form ab initio and finite element method numerical simulations, i) the injection of ions from the NPs to the matrix, ii) the surface migration‐induced NP reshaping, and iii) the NP migration and consequent percolation path adjustments are shown. The implications of this study are significant for the development of ultrafast soft ionic actuators and create the premises for a broad range of applications in smart materials and devices. Abstract : A new phenomenon, the converse piezo‐electro‐kinetic (CPEK) effect, is described: a nonequilibrium electric‐field‐driven surface atom drift able to introduce structural anisotropy on former spherical metallic nanoparticles, resulting in an elongation of the whole nanocomposite hundred‐fold times the electrostriction effect. The CPEK effect exploits ultrafast response up to 1 kHz and reversibility, having therefore profound implications as a brand new actuation technology.